Antithrombin Perfluorocarbon Nanoparticles Improve Renal Allograft Function in a Murine Deceased Criteria Donor Model. Issue 9 (September 2018) - Vemuri, Chandu; Upadhya, Gundumi A.; Arif, Batool; Jia, Jianluo; Lin, Yiing; Gaut, Joseph P.; Fazal, Jawad; Pan, Hua; Wickline, Samuel A.; Chapman, William C.
Abstract : Background: Over 100 000 patients await renal transplantation and 4000 die per year. Compounding this mismatch between supply and demand is delayed graft function which contributes to short-term and long-term graft failures. Previously, we reported that thrombin-targeted perfluorocarbon nanoparticles (PFC-NP) protect kidneys from ischemic renal injury after transient arterial occlusion. Here we hypothesize that perfusion of renal allografts with PFC-NP similarly can protect graft function after an ischemic interval. Methods: After 60 minutes of warm ischemia, male Lewis rats underwent left renal explantation followed by renal perfusion with 5 mL of standard perfusate alone (N = 3) or with 0.3 mL of untargeted PFC-NP (N = 5) or 0.3 mL thrombin-targeted of PFC NP functionalized with phenylalanine-proline-arginine-chloromethylketone (PPACK) (PFC-PPACK), an irreversible thrombin inhibitor (N = 5). Kidneys underwent 6 hours of cold storage, followed by transplantation into recipients and native nephrectomy. Animals were euthanized at 24 hours for tissue collection or at 48 hours for blood and renal tissue collection. A survival experiment was performed using the same protocol with saline control (N = 3), PFC-NP (N = 3) or PFC-PPACK (N = 6). Results: Serum creatinine was improved for the PFC-PPACK groups as compared with control groups ( P < 0.04). Kaplan-Meier survival curves also indicated increased longevity ( P < 0.05). Blinded histologic scoring revealed markedly attenuated renal damage in the PFC-PPACK group compared to untreated animals (2.75 ± 1.60 versus 0.83 ± 3.89; P = 0.0001) and greater preservation of renal vasculature. Conclusions: These results validate an NP-based approach to improve renal graft function as antithrombin NPs improved allograft function, decreased renal damage, protected vasculature, and improved longevity.